Given that 3 x − y = 1 2 , solve for 2 y 8 x .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Solve for y in terms of x then substitute:
3 x − y = 1 2 ⟹ y = 3 x − 1 2
Substitute:
2 y 8 x = 2 3 x − 1 2 2 3 x = 2 3 x 2 − 1 2 2 3 x = 2 − 1 2 1 = 2 1 2 1 1 = 1 1 × 1 2 1 2 = 2 1 2 = 4 0 9 6
Did you mean y = 3 x − 1 2 ?
2 y 8 x = 2 y ( 2 3 ) x = 2 y 2 3 x . Since it is given that 3 x − y = 1 2 , it concludes that 3 x = 1 2 + y . Therefore, 2 y 2 3 x becomes 2 y 2 1 2 + y , or 2 y 2 1 2 ⋅ 2 y , or 2 1 2 , or 4 0 9 6 .
Problem Loading...
Note Loading...
Set Loading...
Similar solution as @Michael Wang 's, presented as follows:
2 y 8 x = 2 y 2 3 x = 2 3 x − y = 2 1 2 = 4 0 9 6 Given that 3 x − y = 1 2